Enterobactin induces the chemokine, interleukin-8, from intestinal epithelia by chelating intracellular iron. Issue 1 (9th November 2020) - Saha, Piu; Yeoh, Beng San; Xiao, Xia; Golonka, Rachel M.; Abokor, Ahmed A.; Wenceslau, Camilla F.; Shah, Yatrik M.; Joe, Bina; Vijay-Kumar, Matam
ABSTRACT: Iron is an indispensable nutrient for both mammals and microbes. Bacteria synthesize siderophores to sequester host iron, whereas lipocalin 2 (Lcn2) is the host defense protein that prevent this iron thievery. Enterobactin (Ent) is a catecholate-type siderophore that has one of the strongest known affinities for iron. Intestinal epithelial cells (IECs) are adjacent to large microbial population and are in contact with microbial products, including Ent. We undertook this study to investigate whether a single stimulus of Ent could affect IEC functions. Using three human IEC cell-lines with differential basal levels of Lcn2 ( i.e . HT29 < DLD-1 < Caco-2/BBe), we demonstrated that iron-free Ent could induce a dose-dependent secretion of the pro-inflammatory chemokine, interleukin 8 (IL-8), in HT29 and DLD-1 IECs, but not in Caco-2/BBe. Ent-induced IL-8 secretion was dependent on chelation of the labile iron pool and on the levels of intracellular Lcn2. Accordingly, IL-8 secretion by Ent-treated HT29 cells could be substantially inhibited by either saturating Ent with iron or by adding exogenous Lcn2 to the cells. IL-8 production by Ent could be further potentiated when co-stimulated with other microbial products (i.e. flagellin, lipopolysaccharide). Water-soluble microbial siderophores did not induce IL-8 production, which signifies that IECs are specifically responding to the lipid-soluble Ent. Intriguingly, formyl peptide receptor (FPR) antagonists (i.e. Boc2, cyclosporine H) abrogated Ent-induced IL-8, implicating that such IEC response could be, in part, dependent on FPR. Taken together, these results demonstrate that IECs sense Ent as a danger signal, where its recognition results in IL-8 secretion. Graphical abstract: